A Conceptual Framework of Cultural Heritage-Based Tourism Income Generation: Insights from Pura Desa Sukawati, Bali - Ni Kadek Muliati; Ni Made Sudarmini; Ni Wayan Sukartini; Putu Esa Naranata Dewi (Journal of Tourism Economics and Policy, 2026)
Cultural heritage has increasingly been recognized as a strategic asset for sustainable tourism development because it not only preserves cultural identity but also contributes to local economic development. This study aims to develop a conceptual framework that explains the relationship between cultural heritage, heritage-based tourism activities, visitor experiences, tourism income generation, and heritage conservation, using Pura Desa Sukawati in Bali as a contextual illustration. The study employed a qualitative conceptual research design using an integrative literature review. Relevant literature published between 2020 and 2025 was critically synthesized through conceptual content analysis by integrating Heritage Tourism Theory, Community-Based Tourism, the Tourism Multiplier Effect, the Experience Economy, and Sustainable Tourism. The analysis proposes an integrated conceptual framework demonstrating that cultural heritage functions as the foundation of heritage-based tourism activities, which create meaningful visitor experiences and stimulate tourism expenditure. These expenditures generate direct, indirect, and induced economic benefits that enhance community welfare while providing financial support for heritage conservation and long-term destination sustainability. The proposed framework contributes to the heritage tourism literature by integrating cultural, economic, and conservation perspectives into a single analytical model. Practically, the framework provides strategic insights for policymakers, heritage managers, and local communities in designing tourism policies that balance economic development with the preservation of cultural authenticity and sacred heritage values. Future empirical studies are recommended to validate the proposed framework in various cultural heritage destinations.